Exploring the Influence of a Single Bout of Tahajjud Prayer on Acute Blood Pressure Response in Normotensive Young Adult Males with Varied Regularity of Tahajjud Practice - Yusni Yusni; Hanifah Yusuf; Mustanir Yahya (Islamic Guidance and Counseling Journal, 2023)
Tahajjud, a type of sunnah worship for Muslims, involves standard rules and complex movements that contribute to cardiovascular health and blood pressure regulation. Aims and scope: This study aimed to analyze the effect of a single bout of tahajud, on systolic (SBP) and diastolic blood pressure (DBP) in normotensive young men. The study employed an experimental design with healthy men aged 18-25 and normal blood pressure (normotensive). It included a control group (n = 12) that did not perform Tahajjud and a trial group (n = 12) that regularly practiced Tahajjud for over six weeks. The treatment involved performing Tahajjud consisting of 11 raka'at from 3:30-4:30 a.m., lasting 25-35 minutes. Blood pressure was measured using a sphygmomanometer before and after Tahajjud, and data analysis utilized a t-test (p < .05). These findings indicate that there is a non-significant difference in the mean of SBP and DBP after midnight between the control and trial groups, SBP (mmHg): 110.42±9.16 and 114.58±4.98 vs 120±6.03, p = .11 and 115±6.74, p = .08. DBP (mmHg): 76.77±4.92 and 77.50±4.52, p = .58 vs. 81.67±8.35 and 79.17±5.15, p = .19, SBP and DBP decreased by 5 mmHg and 2.5 mmHg in the trial group. Tahajjud, regardless of regularity, can elicit a modest but non-significant reduction in both SBP and DBP. These results indicate that Tahajjud may have a potential role in promoting cardiovascular health. Further research is warranted to examine the long-term effects and underlying mechanisms of Tahajjud on BP regulation.